Profile of the physical condition of female adolescent volleyball athletes - Titi Harianti; Sukardi Sukardi; Farizal Imansyah (Sriwijaya Journal of Sport, 2021)
The purpose of this study was to determine the level of physical condition of adolescent volleyball players in SMP Negeri 01 Kisam Tinggi. This type of research is a qualitative descriptive study with a research sample of 12 teenage female volleyball players. The components of physical condition measured in this study were aerobic endurance, arm muscle strength endurance, speed, leg muscle explosive power, and agility. The instrument in this study used the Indonesian Physical Fitness Test for 13-15 Years Old. The results showed that the physical condition of female volleyball athletes in their teens at SMP Negeri 01 Kisam Tinggi was categorized in the moderate category. From the results of these studies, it is necessary to use a suitable exercise method by taking into account the characteristics of the research sample to improve the physical condition of female adolescent volleyball athletes.